2022
DOI: 10.3389/fped.2022.778378
|View full text |Cite
|
Sign up to set email alerts
|

Using Aggregate Vasoactive-Inotrope Scores to Predict Clinical Outcomes in Pediatric Sepsis

Abstract: ObjectivesThe heterogeneity of sepsis makes it difficult to predict outcomes using existing severity of illness tools. The vasoactive-inotrope score (VIS) is a quantitative measure of the amount of vasoactive support required by patients. We sought to determine if a higher aggregate VIS over the first 96 h of vasoactive medication initiation is associated with increased resource utilization and worsened clinical outcomes in pediatric patients with severe sepsis.DesignRetrospective cohort study.SettingSingle-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…Previous studies have identified factors associated with cardiopulmonary arrest in critically ill children. Previous studies have demonstrated ST-segment variability, vasoactive-inotrope score, higher inadequate oxygen delivery index, venous saturation, serum lactate, cerebral dysfunction by electroencephalography, a history of a previous cardiac arrest, specific cardiac lesions, and specific cardiac surgeries among others[ 3 4 5 6 7 8 9 10 11 12 13 14 15 16 ] as risk factors for adverse outcomes. Risk factors for mortality have often mirrored the risk factors for cardiac arrest.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified factors associated with cardiopulmonary arrest in critically ill children. Previous studies have demonstrated ST-segment variability, vasoactive-inotrope score, higher inadequate oxygen delivery index, venous saturation, serum lactate, cerebral dysfunction by electroencephalography, a history of a previous cardiac arrest, specific cardiac lesions, and specific cardiac surgeries among others[ 3 4 5 6 7 8 9 10 11 12 13 14 15 16 ] as risk factors for adverse outcomes. Risk factors for mortality have often mirrored the risk factors for cardiac arrest.…”
Section: Discussionmentioning
confidence: 99%
“…Specific to PICU, however, literature characteristically demonstrates poor outcomes in the backdrop of high hemodynamic support. 4 , 5 Employing described formulas like vasoactive-inotropic score (VIS) for reporting cardiovascular support, Musick et al highlight an escalating relative risk of mortality alongside an increasing VIS in PICU. 4 Adding to the debate and propounding an update of the cvSOFA, Pölkki et al recently discover an improved mortality predictive accuracy of the SOFA score on replacing the cvSOFA with maximum VIS or the VIS max , in a setting involving 8,079 ICU patients with a 30-day mortality rate of 13%.…”
mentioning
confidence: 99%
“… 1 To that end, a retrospective cohort study by Shah et al outlines the merit of estimating the aggregate VIS, computed using the hourly VIS area under the curve calculation premised on the trapezoidal rule. 5 Amidst an elevated aggregate VIS being associated with in-hospital mortality and the need for continuous renal replacement therapy (CRRT) and extracorporeal membrane oxygenation (ECMO) ( p < 0.0001, for all the parameters), classification and regression tree (CART) analysis revealed aggregate VIS >16 and >20 as respective independent predictors of ECMO use and in-hospital mortality ( p < 0.0001). 5 Indeed, the role of catering to outcomes like ECMO or CRRT in a prospective observational PICU-based study like the one by Lois and Save, can also not be overemphasized.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting score had an area under the curve of 0.84 with an optimal Previous studies have identi ed factors associated with cardiopulmonary arrest in critically ill children. Previous studies have demonstrated ST-segment variability, vasoinotrope score, higher inadequate oxygen delivery index, venous saturation, serum lactate, cerebral dysfunction by electroencephalography, a history of a previous cardiac arrest, speci c cardiac lesions, and speci c cardiac surgeries among others[3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Risk factors for mortality have often mirrored the risk factors for cardiac arrest.…”
mentioning
confidence: 99%